Associations Between Pet Ownership and Attitudes Toward Pets With Youth Socioemotional Outcomes - Jacobson, Kristen C.; Chang, Laura (Frontiers in Psychology, 2018)
Evidence regarding the effects of pet ownership and related variables on youth socioemotional development is mixed. Inconsistencies across studies may be due to a variety of factors, including the use of different outcomes measured across studies, small potential effect sizes, and use of selected samples. In addition, studies have not systematically controlled for demographic characteristics that may bias results, nor have studies systematically examined whether effects are consistent across different subgroups. The present study examined the impact of pet ownership and attitudes towards pets on four measures of youth socioemotional outcomes: delinquency, depressed mood, empathy, and prosocial behavior. Linear mixed-effect regression analyses were conducted on 342 youth (48.0% male) aged 9 to 19 (M = 14.05, SD = 1.77) from a racially, ethnically, and socioeconomically diverse sample. The majority (59.1%) of youth currently lived with a dog or cat and all participants completed the Pet Attitude Scale-Modified. Pet owners reported lower delinquency and higher empathy than non-owners; however, group differences became non-significant once demographic factors were controlled for. Attitudes towards pets was significantly associated with all four outcomes. More positive attitudes was modestly associated with lower delinquency (β = -0.22, p < .001) and higher empathy (β = 0.31, p < .001), with smaller effects for depressed mood (β = -0.12, p = .035) and prosocial behavior (β = 0.12, p = .021). For delinquency, empathy, and prosocial behavior, effects were only slightly attenuated and remained statistically significant after controlling for gender, age, race/ethnicity, family socioeconomic status, and pet ownership, although the effect for depressed mood became nonsignificant after inclusion of these demographic factors. While there was some variability in effect sizes across different subgroups, none of the interactions between attitudes towards pets and gender, race/ethnicity, age, family SES, or pet ownership was statistically significant, indicating that the effects may transcend individual differences in demographic characteristics. Overall, the study adds to a growing body of work supporting a positive relationship between emotional bonds with pets and youth socioemotional outcomes and offers potential explanations for inconsistencies across previous studies.